Horticultural Hall, 101 Tremont Street, ca. 1880-90 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest of Horticultural Hall on Tremont Street between Bosworth Street on the left and Bromfield Street on the right. Statues adorn the building. In the foreground are street lights and wires. Imbedded in the street are the tracks the electric railway cars run on. 7 1/2 x 9 1/2 Photographs